Marketing Strategy of Tourism Destination Mas Harun Bastari Lake, Rejang Lebong Regency - Yanto Effendi; Sri Narti (Kusuma Negara Business School, 2020)
The purpose of this study was to determine the marketing strategy of tourism destination the Mas Harun Bastari Lake, Mujerejo Village, Rejang Lebong Regency. The results of the study using a SWOT analysis obtained IFAS values (Strength: 14.30, Weaknesses: 4.81). EFAS Value (Opportunity: 1.31, Treats: 1.08). In the SWOT diagram the values for Strength and Weaknesses are at 9.49 and the meeting point for Opportinity and Threats is at 0.23, this shows that they are in quadrant 1, which supports aggressive strategies, which is a very profitable situation, by taking advantage of opportunities and strengths there is. Marketing strategies for the Lake Mas Harun Bastari tourism destination, Mujerejo Village, Rejang Lebon g Regency that can be done are renovating the lake area, adding facilities such as fishing locations and outbound equipment for visitors, placing security personnel in the lake area, giving permission to the community who will conduct activities on location, making agro tourism that can be enjoyed by visitors at the lake location, making a unique arrangement in the lake area, which differentiates it from other tourist attractions, providing comfort for visitors while in the lake area, adding a playground around the lake area, placing personnel who are always maintain cleanliness of the location, make warning signs around the lake location and put up evacuation signs around the site in the event of a disaster.